Metoclopramide-induced acute oculogyric crisis treated with biperiden: A case report - Saponara, Riccardo; Domina, Elisabetta (Indian Journal of Case Reports, 2019)
Metoclopramide is an antiemetic prescribed in general medical practice. The drug can cause acute dystonic reactions. Here, we described the case of a 23-year-old young woman with a chief complaint of blurred vision and later dystonic, oculogyric-type crisis. She underwent laboratory tests and neuroimaging then was hospitalized in the Neurological Department. Treatment with intravenous biperiden interrupted the oculogyric crisis. Only a thorough drug history and correct clinical examination can discover the use of metoclopramide-induced adverse drug reaction such as oculogyric crisis.